Some Noiseless Coding Theorems of Inaccuracy Measure of Order α and Type β - Baig, M. A. K.; Dar, Rayees Ahmad (Sarajevo Journal of Mathematics, 2024)
In this paper, we propose a parametric `useful' mean code length which is weighted by utilities and generalizes some well known mean code lengths available in the literature. The object of this paper is to establish some results on noiseless coding theorems for the proposed parametric `useful' mean code length in terms of generalized "useful" inaccuracy measure of order α and type β. 1991 Mathematics Subject Classification. 94A17, 94A24